Magnetic and structural depth profiles of Heusler alloy Co2FeAl0.5Si0.5 epitaxial films on Si(1 1 1). (17th January 2018) - Glover, Stephanie E; Saerbeck, Thomas; Kuerbanjiang, Balati; Ghasemi, Arsham; Kepaptsoglou, Demie; Ramasse, Quentin M; Yamada, Shinya; Hamaya, Kohei; Hase, Thomas P A; Lazarov, Vlado K; Bell, Gavin R
Abstract: The depth-resolved chemical structure and magnetic moment of C o 2 F e A l 0.5 S i 0.5, thin films grown on Si(1 1 1) have been determined using x-ray and polarized neutron reflectometry. Bulk-like magnetization is retained across the majority of the film, but reduced moments are observed within 45   A ˚ of the surface and in a 25   A ˚ substrate-interface region. The reduced moment is related to compositional changes due to oxidation and diffusion, which are further quantified by elemental profiling using electron microscopy with electron energy loss spectroscopy. The accuracy of structural and magnetic depth-profiles obtained from simultaneous modeling is discussed using different approaches with different degree of constraints on the parameters. Our approach illustrates the challenges in fitting reflectometry data from these multi-component quaternary Heusler alloy thin films.